2023
DOI: 10.4236/ojvm.2023.136006
|View full text |Cite
|
Sign up to set email alerts
|

Association between Infrared Thermography, Blood Count and Creatine Kinase in the Evaluation of the Welfare of Vaquejada Horses

Abstract: The Quarter-Horses regularly participate in non-traditional sports that simulate activities on cattle ranches. In the vaquejada races, the horses run at about 30 km/h, reaching maximum heart rates of around 200 bpm, indicating the great physical effort during competitions and with that could impact welfare. To test the hypothesis that vaquejada horses can be evaluated for the quality of welfare through a combination of non-invasive and invasive methods, an experiment was developed that aimed to assess the qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…However, it has been observed that there are no increases in cortisol, IL-6, or IL-1β because of physical exertion. This is consistent with previous research on quarter horses that participated in vaquejada [2,19], a sport like 3TB running in terms of its high intensity and short duration.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, it has been observed that there are no increases in cortisol, IL-6, or IL-1β because of physical exertion. This is consistent with previous research on quarter horses that participated in vaquejada [2,19], a sport like 3TB running in terms of its high intensity and short duration.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, the results are important because they indicate that there is no inflammation caused by the bits and harnesses commonly used in this equestrian sport, provided they comply with the official rules. Similar results were observed in these areas in vaquejada horses [2], where no changes in local temperature were observed.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations